2013
DOI: 10.1016/j.biombioe.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Von Rittinger theory adapted to wood chip and pellet milling, in a laboratory scale hammermill

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. b s t r a c tThe study draws upon the milling theories developed for the ore processing industry (Von Rittinger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
5
32
1
Order By: Relevance
“…The specific comminution energy is increasing in the hammer mill by the power law with a greater size reduction. These results are contrary to the ones presented by Temmerman et al [20] who found a linear relation between specific comminution energy and size reduction, using the expression of the Rittinger theory to describe the size reduction. The difference in the functional relations possibly can be explained by the different approaches of comminution.…”
Section: Functional Relations Between Specific Comminution Energy Andcontrasting
confidence: 99%
See 1 more Smart Citation
“…The specific comminution energy is increasing in the hammer mill by the power law with a greater size reduction. These results are contrary to the ones presented by Temmerman et al [20] who found a linear relation between specific comminution energy and size reduction, using the expression of the Rittinger theory to describe the size reduction. The difference in the functional relations possibly can be explained by the different approaches of comminution.…”
Section: Functional Relations Between Specific Comminution Energy Andcontrasting
confidence: 99%
“…Miao et al [24] proposed a power type function for the relation between energy consumption and screen diameters used in comminution of miscanthus, switchgrass, and willow in a hammer and cutting mill. The work of Temmerman et al [20] is the first study which tries to develop a comminution theory for wood, by adapting existing milling theories developed for the ore processing industry (Von Rittinger, Kick and Bond theories) to the comminution of wood chips. They found that the relation between comminution energy and size reduction can be best described by the Rittinger theory which is a linear relation.…”
Section: Introduction and Scope Of Workmentioning
confidence: 99%
“…In previous study, Karinkanta et al also reported linear relationship between the inverse value of 50 of finely ground wood powder and total available impact energy with oscillatory ball mill in accordance to Rittinger's model [29]. The model constant C can be a good indicator for grindability of woody biomass, and for evaluating the energy efficiency of milling process when similar materials are used as a probe [46]. in Rittinger's model for various initial size samples is shown in Fig.…”
Section: Analysis Of Energy Requirements For Size Reductionmentioning
confidence: 53%
“…The layer structure also results in a heterogeneous distribution of chemical compositions (i.e., cellulose, hemicellulose and lignin) at cellular level. Mechanically fragmenting the lignocellulosic biomass is a process that disintegrates the cellular integrity of heterogeneous composites by generating new surface area (Temmerman et al, 2013). Thus, the SSA of cellulose is closely linked to cell wall fracture and resulting composition exposure on the newly generated surface.…”
Section: Specific Surface Area Of Cellulose In Micronized Woodmentioning
confidence: 99%